The transition of print media in a digital format (Herald of Journalism, 2020)
This article focuses on the transition of print media in electronic for mat. The author examines the trends in the development of publications in the country and abroad, and their development in the global network – the Internet. The development new technologies and the Internet is enabling the publication of newspapers and magazines in the world wide web. The article discusses the possibility of such a transition in Kazakhstan, with examples of newspapers and websites.
Keywords: publications, media, electronic format, website.